Research Trend on Organizational Citizenship Behavior (OCB) through Bibliometric Analysis - Nugraha Putri, Nita Novia; Arafah, Riqif; Ayu Murti, Intri; Andleeb, Naima (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2024)
Purpose - This article aims to provide an overview and synthesis of the existing body of knowledge about Organizational Citizenship Behavior (OCB). Through bibliometric analysis from 2018 to 2023, special attention is paid to articles directly related to OCB and to Indonesia's contribution to their publications. Design/methodology/approach- A bibliographic analysis was carried out on 500 articles from the Google Scholar database using Publish or Perish software version 8, followed by VOSViewer. Originality - Previous studies have provided a systematic review of the literature using different approaches, but the intellectual structure and evolution of research on OCB need to be described. This article presents an overview, synthesis, and analysis of the extent of research related to OCB worldwide. Findings and Discussion - This research provides a comprehensive picture of the development of OCB literature, documenting the output of publications related to OCB, identifying research trends on OCB globally, and examining Indonesia's contribution during the 2018-2023 period. Conclusion - This research describes the growth of OCB research, identifies significant research trends, and highlights Indonesia's important contributions to that literature. These findings provide an in-depth view of the importance of understanding organizational behavior in the context of various organizations and Indonesia's important role in the development of global knowledge in the field of OCB.